2010
DOI: 10.1002/ajmg.a.33249
|View full text |Cite
|
Sign up to set email alerts
|

Unbalanced 3;22 translocation with 22q11 and 3p deletion syndrome

Abstract: This report describes a 25-day-old Turkish boy with unbalanced 3;22 translocation that includes the 22q11.2 deletion and 3p25 deletion syndrome. The karyotype was 45, XY,der(3)t(3;22)(p25;q11),-22. Although no immunological dysfunction could be demonstrated, the boy presented some manifestations of DiGeorge anomaly (DGA), which has been associated with monosomy for the same region of chromosome 22, velocardiofacial syndrome (VCFS), and the 3p deletion syndrome. Clinical features include short stature, hypertel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Although skeletal anomalies are not a defining feature of DiGeorge syndrome, rare cases of lower limb defects including talipes equinovarus have been described in chromosome 22q11 deletions. [45][46][47] Finally, we detected two individuals with Klinefelter's syndrome (XXY) who were not previously known to have this disorder. Like the other individuals in this study, these individuals presented with isolated talipes equinovarus, and are cognitively and physically normal at 45 years follow-up.…”
Section: Clinically Relevant Recurrent Cnvs Identified In Talipes Equmentioning
confidence: 94%
“…Although skeletal anomalies are not a defining feature of DiGeorge syndrome, rare cases of lower limb defects including talipes equinovarus have been described in chromosome 22q11 deletions. [45][46][47] Finally, we detected two individuals with Klinefelter's syndrome (XXY) who were not previously known to have this disorder. Like the other individuals in this study, these individuals presented with isolated talipes equinovarus, and are cognitively and physically normal at 45 years follow-up.…”
Section: Clinically Relevant Recurrent Cnvs Identified In Talipes Equmentioning
confidence: 94%
“…A limited number of patients with atypical deletions (Fig. 1) or translocations have been described [Kurahashi et al, 1996;Jaquez et al, 1997;Garcia-Minaur et al, 2002;Rauch et al, 2005;D'Angelo et al, 2007;Fernandez et al, 2009;McGoey and Lacassie, 2009;Dundar et al, 2010;Yu et al, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…Two more studies reported patients with chromosomal abnormalities involving the short arm of chromosome 3 at 3p25 and the long arm of chromosome 22 at 22q11. Respectively, Dundar et al [2010] reported a patient with developmental delay and a de novo karyotype, 45,X,der(3) t(3; 22)(p25;q11),-22, while Faed et al [1987] described a child with de novo monosomy for chromosomes 22 22q11.2 deletion syndrome (also known as DiGeorge syndrome) is one of the most common microdeletion syndromes in the community. Its prevalence is known as 1/4,000, but with new studies, it is stated that the 22q11.2 deletion is more common than estimated [Grati et al, 2015].…”
Section: Discussionmentioning
confidence: 99%